Complex Coacervation of Plant-Based Proteins and Polysaccharides: Sustainable Encapsulation Techniques for Bioactive Compounds - Mohammad Alrosan (20089263) (2025)
Complex coacervation is a phase separation phenomenon between two oppositely charged colloids, such as proteins and polysaccharides, when mixed in a solution. The attractive forces between the oppositely charged particles lead to the formation of a coacervate phase, which is a liquid, dense, and polymer-rich phase. Animal-based proteins and polysaccharides are commonly used to prepare high-quality bioactive compounds and are widely used to produce complex coacervations with desirable physicochemical properties. During complex coacervation, utilizing animal-based proteins, such as casein, offers several advantages. However, challenges and concerns are associated with their production, including high costs, environmental impact, the spread of animal diseases, and the emergence of drug-resistant pathogens. As an alternative to animal-based proteins, plant-based proteins are gaining traction in complex coacervation, addressing several challenges associated with animal-based protein production. Plant-based proteins provide a range of benefits that align with environmental sustainability, cost-effectiveness, and reduced concerns about animal diseases. Some key advantages of employing plant-based proteins in complex coacervation include sustainability, biocompatibility, reduced ecological impact, disease resistance, diversity of sources, consumer demand, and allergen considerations. Various physical, chemical, and biological processes are employed to enhance the characteristics of plant-based protein-polysaccharide coacervates. This comprehensive review elucidates recent advancements in the microencapsulation of bioactive compounds through complex coacervation utilizing plant-based protein-polysaccharide systems. This review serves as a valuable resource for summarizing the current state of research, identifying limitations and gaps in knowledge, and discussing challenges within the field. Other Information Published in: Food Engineering Reviews License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s12393-025-09408-7